This I Believe - Weil, Frank L. (Frank Leopold) (Tufts Archival Research Center, 2006)
Frank Weil describes his beliefs that one must earn future privileges through the work of today, that belief in the future provides strength for meeting the challenges of today, and that people in general have the wisdom and integrity to achieve a better tomorrow.